The activity of SnRK1 is increased in Phaseolus vulgaris seeds in response to a reduced nutrient supply - Coello, Patricia; Martínez-Barajas, Eleazar (Frontiers in Plant Science, 2014)
Abstract Phaseolus vulgaris seeds can grow and develop at the expense of the pod reserves after the fruits have been removed from the plant (Fountain et al., 1989). Because this process involves sensing the reduction of nutrients and the remobilisation of pod reserves, we investigated the effect on SnRK1 activity during this process. Bean fruits removed from the plant at 20 days after flowering (DAF) demonstrated active remobilisation of nutrients from the pod to the seeds. After five days, the pod dry weight was reduced by 50%. The process was characterised by a rapid degradation of starch, with the lower level observed on day 1 after the fruits were removed. However, the pod nutrients were insufficient for the needs of all the seeds; only some seeds continued their development. Those seeds exhibited a transient reduction in sucrose levels on day 1 after the fruits were removed. However, the normal level of sucrose was recovered, and the rate of starch synthesis was identical to that of a seed developed under normal conditions. Removing the fruits from the plant had no effect on SnRK1 activity in the pods, whereas in the seeds, the activity increased by 35%. The increase in SnRK1 activity was observed in both the cotyledon and embryo axes, but it was higher in the cotyledon. In cotyledon, the increment of SnRK1 activity correlates with the abundance of the phosphorylated catalytic subunit, whereas in the embryo axes the mechanism of activation seems to be different. It is possible that the increase in SnRK1 activity observed in seeds developed in fruits that have been removed from the plant is part of the mechanism required to favour seed development under conditions of stress.